To solve the equation \( 25x^2 - 196 = 0 \) by factoring using the difference of squares pattern, we first recognize that this can be expressed as a difference of squares:
\[ 25x^2 - 196 = (5x)^2 - (14)^2 \]
Now we can use the difference of squares formula \( a^2 - b^2 = (a - b)(a + b) \):
\[ (5x - 14)(5x + 14) = 0 \]
Next, we set each factor equal to zero:
- \( 5x - 14 = 0 \)
- \( 5x + 14 = 0 \)
Solving the first equation:
\[ 5x - 14 = 0 \implies 5x = 14 \implies x = \frac{14}{5} \]
Solving the second equation:
\[ 5x + 14 = 0 \implies 5x = -14 \implies x = -\frac{14}{5} \]
Thus, the solutions to the equation \( 25x^2 - 196 = 0 \) are:
\[ x = \frac{14}{5} \quad \text{and} \quad x = -\frac{14}{5} \]
Among the response options provided, the correct solution(s) are:
- \( x = -\frac{14}{5}, x = \frac{14}{5} \)